THE EFFECTIVENESS OF COLLOID MODULE BASED ON GUIDED INQUIRY APPROACH TO INCREASE STUDENTS’ COGNITIVE LEARNING OUTCOMES - Novilia, Lita; Iskandar, Srini M.; Fajaroh, Fauziatul (International Journal of Education, 2016)
Colloid is one of the chemical topics taught in high school. Actually, the characteristic of Colloid topic is contextual. Colloid topic is taught by expository and discussion methods. Based on observations in SMA Negeri 4 Malang and SMA Negeri 16 Surabaya, these methods could not improve students’ ability to construct their own knowledge; as a result, students did not have a good understanding in the Colloid topic. An alternative way to increase students’ understanding, especially in the cognitive aspect is using innovative teaching materials like a colloid module based on guided inquiry approach. The previously mentioned module was developed by the author. The feasibility percentage of the Module was 85.66%. The aim of this research is to find the effectiveness of the Colloid Module to increase students’ cognitive learning outcomes. This research used one group pretest-posttest experimental design. The sample of this research consisted of 33 students of X-MIPA 3 SMA Negeri 2 Malang in the 2015/2016 academic year. The effectiveness of The Colloid Module to increase cognitive learning outcomes was determined by the results of paired sample t-test analysis and the gain score of students’ pretest and posttest using cognitive test instrument. This cognitive test instrument had content validity index of 92.04%. Based on the trial result of 36 students in SMA Negeri 3 Malang, 30 questions were considered valid and had a reliability coefficient of 0.866 based on Spearman-Brown. The result of this research showed that the Colloid Module was effective to increase students’ cognitive learning outcomes. It was indicated by the analysis of paired sample t-test, with t score (-38.525) lower than t critical (-2.037), so there was a significant difference between pretest and posttest scores after using the Colloid Module. The effectiveness of the Colloid Module was also determined by the gain score of pretest and posttest scores of students’ cognitive skills of 0.688, categorized as a medium gain.